Human development and quality of life of Colombian designers in the Creative Economy - Ramírez Gil, Felipe (2024)
The human development and quality of life of the Colombian designer in light of the Comprehensive Policy for the Creative Economy promoted by the Colombian state are analyzed in this article. Following what is established by the capabilities approach, a reflection is made about the attention that Public Policy has on the functioning and capabilities that allow Colombian designers to improve their quality of life through their professional activity. Thanks to the analysis of multiple legal documents under the capabilities approach, it is concluded that the lack of attention to the person and their professional circumstances is a great gap in the state strategy that must be filled in a timely manner, particularly the central capacity of Affiliation.